Characterization and differential nuclear localization of Nopp140 and a novel Nopp140-like protein in trypanosomes. - Kelly, S; Singleton, W; Wickstead, B; Ersfeld, K; Gull, K (2006)
Trypanosomatids possess two homologues of Nopp140: a canonical Nopp140 and a Nopp140-like protein (TbNoLP) in which a GAR domain replaces the C-terminal SRP40 domain. Both are phosphorylated and coimmunoprecipitate with RNA polymerase I. Each paralogue has a distinct subnuclear localization, and depletion of TbNoLP produces an enlarged nucleolus in which TbNopp140-containing regions disperse. The restricted occurrence pattern of NoLP proteins reflects an intriguing convergence in evolution, suggestive of a function in nucleoplasmic small nucleolar ribonucleoprotein shuttling.